AKURASI SISTEM PENENTUAN AWAL WAKTU SHALAT MENURUT KITAB FATHULLATHÎFRRAHÎM DENGAN SISTEM KONTEMPORER - Niskaromah, Niskaromah; Mutaqqin, Faizul (Journal of Innovation Research and Knowledge, 2023)
The Book of Fathullathîfurrahîm authored by KH Abdul Muhaimain and written by KH Ahmad Gozali Asyiq who was his student. A book of astronomy was taught at the BANY SYAFI'I Islamic boarding school, located in Palas Bendungan, Cilogon District, Banten. The book is as reference for determining the start of prayer times without the help of modern tools such as scientific calculators. A scientific culture that is relatively rare in a information technology era but there is still a scientific discipline that is applied very manually. Even though it seems impractical, (of course it is not only seen from a pragmatic point of view), but is appreciated for its scientific value which is the basis for determining the initial digital prayer times which has become a general reference. As a form of scientific treasure, the existence of the book Fathullathîfurrahîm فتح اللطيف الرحيم should be appreciated. However, comparisons of the provisions based on the book with the technology-based prayer times should also be examined to find out the accuracy. The accuracy of the results will impact harmonization for those who follow the time schedule based on the book and those who use a technology-based prayer time schedule. This study used a qualitative method with an arithmetic approach using data collection techniques, library research and interviews. Primary data was obtained directly from the Bany Syafi'i Islamic boarding school with reference to the book Fathullathîfurrahîm, while secondary data included all documents in the form of books, books, writings, interview results, papers related to the research object. Analysis technique with inductive analysis, namely from specific facts then abstracted in the form of general conclusions. With descriptive analysis, then compared with other methods to get a systematic, factual, and accurate picture of the phenomenon being investigated. The results of the study show that the reckoning of calculating the start of the prayer time is done manually (not using any tools such as Rubu' Mujayyab) using only the rules from the book Fathullathîfurrahîm. As for the level of accuracy of the initial prayer times in the book with the initial calculation of the contemporary prayer time, the time difference is 0-2 minutes.